Planejamento da cobertura de redes móveis de quarta geração através de metaheurística híbrida - Vieira, Deborah Luisa Detânico (Universidade do Vale do Rio dos Sinos, 2017)
With the constantly demand of voice services and mostly in mobile data, there was the need the development of the mobile services of fourth generation (4G). The pattern Long Term Evolution, developed by the Third Generation Partnership Project (3GPP) was chosen by the International Telecommunications Union (ITU) as technology to attend the requirements of the fourth generation of mobile services. For the mobile operators introduce and apply this new generation in their own existing networks, they need to do an extensive research and planning, even if, in practical means, it is applied using the empirical way. The network planning problem is widely known and studied in computing area as set-covering problem ans classified as NPhard. Due the unique characteristics of network architecture of LTE, this work aims to solve the mobile’s fourth generation planning problem using a mathematics modelling apply to a hybrid metaheuristics, composed with Genetic Algorithm and Tabu Search. It aims solve the coverage problem of a specific region, covering the largest area possible with the fewest number of Base Sations (BS) possible, seeking the best compliance and cost reduction of the LTE network deployment.
Keywords: Metaheurísticas; Busca tabu; Algoritmo genético; Algoritmo híbrido; Recobrimento de conjuntos; Cobertura de redes móveis; LTE; Metaheuristics; Tabu search; Genetic algorithm; Set-covering problem; Mobile networks coverage; LTE; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação